Raw material sourcing in the Middle Paleolithic site of Gruta da Oliveira (Central Limestone Massif, Estremadura, Portugal) (Journal of Lithic Studies, 2016)
The cave site of Gruta da Oliveira is located in the Almonda karst system, at the interface between the Central Limestone Massif of Portuguese Estremadura (CLM) and the adjacent Sedimentary Basin of the River Tagus (TSB). The cave presents a stratification dated to ~37-107 ka containing hearth features, Neanderthal skeletal remains, as well as fauna, microfauna and wood charcoal remains. The lithic assemblages are large and feature a diverse range of raw materials.Knappable lithic raw materials in primary, sub-primary and secondary position in the CLM and the TSB were systematically surveyed and sampled. The characterization of the geological samples was carried out at both the macro- and the microscopic scales and data were systematized under the petroarcheological and “evolutionary chain of silica” approaches.The study of the lithic assemblage from layer 14 (dated to the ~61-93 ka 95.4% probability interval by TL) indicates that the Gruta da Oliveira Neanderthals used quartzite, quartz and flint from sources located less than 30 km away in both the CLM and the TSB.